2021
DOI: 10.3390/jcm10245985
|View full text |Cite
|
Sign up to set email alerts
|

Setting for “Normal” Serum Ferritin Levels in Patients with Transfusion-Dependent Thalassemia: Our Current Strategy

Abstract: This cross-sectional study aimed to establish the association between serum ferritin levels and organ iron overload (IO) and overall morbidity in transfusion-dependent thalassemia (TDT) patients. One hundred and three TDT patients (40.03 ± 9.15 years; 57.3% females) with serum ferritin < 2500 ng/mL were included. IO was assessed by T2* magnetic resonance imaging. Three groups were identified based on mean serum ferritin levels: <500 ng/mL (group 0; N = 32), 500–1000 ng/mL (group 1; N = 43), and 1000–2500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The results indicated that serum levels of ferritin were extremely high in both TM and TI groups, which indicates that iron overload can cause serious health issues in thalassemia patients if left untreated. Iron overload may be a result of blood transfusion and ineffective extramedullary erythropoiesis [35,36].Howover,ferritin elevation may reflect conditions unrelated to iron metabolisms, such as inflammation, liver injury, and steatohepatitis [37].Consistent with our finding, a previous study suggested that IL-6 may increase ferritin synthesis. Also, both ferritin and IL-6 have a significant correlation to affect serum adiponectin, CRP, Hb concentration, and platelet count [38].…”
Section: Discussionsupporting
confidence: 89%
“…The results indicated that serum levels of ferritin were extremely high in both TM and TI groups, which indicates that iron overload can cause serious health issues in thalassemia patients if left untreated. Iron overload may be a result of blood transfusion and ineffective extramedullary erythropoiesis [35,36].Howover,ferritin elevation may reflect conditions unrelated to iron metabolisms, such as inflammation, liver injury, and steatohepatitis [37].Consistent with our finding, a previous study suggested that IL-6 may increase ferritin synthesis. Also, both ferritin and IL-6 have a significant correlation to affect serum adiponectin, CRP, Hb concentration, and platelet count [38].…”
Section: Discussionsupporting
confidence: 89%
“…No difference was found in the frequency of hypogonadism, hypothyroidism, hypoparathyroidism, osteopenia/osteoporosis, arrhythmias, and hepatic cirrhosis among the 3 groups. 7 Chelation therapy was started at the mean age of 7.3 ± 5.1 years; 5.8± 4.3 years; and 6.2 ± 6.7 years, respectively. The difference was not statistically significant between groups of patients (P: 0.25).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus was detected in 15.6%, 7% and 10.7%, respectively (P: 0.487). 7 No information was reported about other abnormalities of glucose homeostasis. MRI pancreatic IOL was comparable among the three groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies evaluated two opposite conditions. The first article by Ricchi et al reported a cross-sectional study and focuses on the feasibility of achieving serum ferritin < 500 ng/mL for several TDT patients under different chelation regimens [ 1 ]. Such a ferritin target, at MRI T2* evaluation, was associated with the absence of significant cardiac and hepatic iron overload (IO) but with a noteworthy proportion of patients showing simultaneous pancreatic IO.…”
mentioning
confidence: 99%